Environmental taxes - Zoran Šinković (Zbornik Radova Pravnog Fakulteta u Splitu, 2013)
Environmental taxes should result in an improvement or prevention of deterioration of the environment. Although more advanced than previously existing Act on Excise Duty on Passenger Cars, Other Motor Vehicles, Vessels and Aircrafts from the 1997th year, the new law will hardly Croatia bring visible environmental benefit. Its application should not be expected to reduce the negative impacts of road traffic on air quality and greenhouse gas emissions until it does not clearly define how it will be at least part of the funds collected under this levy will be spent on measures to encourage the use of say hybrid or electric vehicles. Yet we should not neglect the fact that there is still need to work on educating people about the importance of environmental protection and any measures to be taken in the sphere of environmental protection should follow economic policies with a particular community or a country.